Digital folkcommunication and consumerist practices of the tanajura in Tianguá (CE) (Revista Internacional de Folkcomunicação, 2019)
The research aims to analyze food practices influenced by folk communication studies in contemporary times. Starting from the premise that food is part of human life and the practices that involve this technology-mediated theme have been reconfigured, speeches promoted in digital media bring the reflection of cultural diversity in societies. The study analyzes how the people from the city of Tianguá-Ceará have used the digital media to share their cultural practices in the consumption of tanajura (a type of ant) revealing the ethos of their people in symbolic productions that emphasize the culture and its traditions in a feelingof belonging. Digital social networks have enabled a space of expression and circulation of messages promoting a visibility in the representation of historically marginalized groups. Folkcommunication, Culture, Social digital networks, Tanajura.